Sammy Keyes and the wild things - Van Draanen, Wendelin (Knopf, 2007)
While on her first hiking and camping trip, thirteen-year-old Sammy tries to solve a mystery involving endangered condors while avoiding scorpions, ticks, and embarrassment.